2013
DOI: 10.1371/journal.pone.0075017
|View full text |Cite|
|
Sign up to set email alerts
|

Inactivation of Norovirus on Dry Copper Alloy Surfaces

Abstract: Noroviruses (family Caliciviridae) are the primary cause of viral gastroenteritis worldwide. The virus is highly infectious and touching contaminated surfaces can contribute to infection spread. Although the virus was identified over 40 years ago the lack of methods to assess infectivity has hampered the study of the human pathogen. Recently the murine virus, MNV-1, has successfully been used as a close surrogate. Copper alloys have previously been shown to be effective antimicrobial surfaces against a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
133
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 46 publications
10
133
0
Order By: Relevance
“…The results presented here are consistent with those of Warnes et al, who performed similar experiments using the cultivable surrogate MNV (13,14). For example, both studies reported evidence of a loss of genome integrity upon exposure to coppercontaining alloys.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results presented here are consistent with those of Warnes et al, who performed similar experiments using the cultivable surrogate MNV (13,14). For example, both studies reported evidence of a loss of genome integrity upon exposure to coppercontaining alloys.…”
Section: Discussionsupporting
confidence: 91%
“…Touch surfaces with antimicrobial properties hold promise to control HuNoV environmental transmission. In this study, we provide evidence that both the genome and capsid of HuNoV are rapidly destroyed during exposure to copper-containing surfaces, a finding supported by data from previous studies using the genetically related and cultivable surrogate MNV (13,14).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…) increases viral inactivation (Park et al, 2014;Warnes and Keevil, 2013). Silver (Ag 0 ) NPs resulted in a 4.0 log removal of the UZ1 bacteriophage after 1 h of exposure, whereas 5.4 mg L À1 of ionic silver (Ag þ ) showed a similar 4 log removal after 5 h (De Gusseme et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The use of biocidal surfaces may play a role in preventing infection transmission from contaminated surfaces when combined with stringent cleaning regimes. Laboratory studies have suggested that copper surfaces may be effective against a range of bacteria, fungi, and viruses (8)(9)(10)(11) and that the irreversible pathogen nucleic acid destruction observed may allay fears of biocide resistance (12). A previous study observed that strains of MRSA were killed on copper surfaces in simulated wet-droplet contamination (13).…”
mentioning
confidence: 99%